2016
DOI: 10.1113/jp271858
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal cystine accumulation promotes mitochondrial depolarization and induction of redox‐sensitive genes in human kidney proximal tubular cells

Abstract: Cystine is a disulphide amino acid that is normally generated within the lysosomes through lysosomal-based protein degradation and via extracellular uptake of free cystine. In the autosomal recessive disorder, cystinosis, a defect in the CTNS gene results in excessive lysosomal accumulation of cystine, with early kidney failure a hallmark of the disease. Previously, we demonstrated that silencing of the CTNS gene in kidney proximal tubular epithelial cells (PTECs) resulted in an increase in intracellular cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 55 publications
4
30
0
Order By: Relevance
“…Since the ER represents a major storage of intracellular calcium (Ca 2+ ), alterations in ER homeostasis can lead to the efflux of Ca 2+ . Indeed, we have previously shown that intracellular Ca 2+ levels were increased in CTNS knockdown PTECs . Previous studies have implicated Ca 2+ dependency of iNOS activity and iNOS is twice as active in the presence of Ca 2+ as in its absence …”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Since the ER represents a major storage of intracellular calcium (Ca 2+ ), alterations in ER homeostasis can lead to the efflux of Ca 2+ . Indeed, we have previously shown that intracellular Ca 2+ levels were increased in CTNS knockdown PTECs . Previous studies have implicated Ca 2+ dependency of iNOS activity and iNOS is twice as active in the presence of Ca 2+ as in its absence …”
Section: Discussionmentioning
confidence: 86%
“…Intracellular NO levels were determined in live cells by fluorescence microscopy (Nikon Instruments, Melville, NY, USA) and flow cytometry (BD Biosciences, San Jose, CA, USA) using the NO‐sensitive dye DAF‐FMDA, as described previously …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations